The response of soil respiration to thinning was not affected by understory removal in a Chinese fir (Cunninghamia lanceolata) plantation - Li, Renshan; Zheng, Wenhui; Yang, Qingpeng; Zhang, Weidong; Chi, Yonggang; Wang, Peng; Xu, Ming; Guan, Xin; Chen, Longchi; Wang, Qingkui; Wang, Silong (Geoderma, 2019)
Thinning and understory removal are two common silvicultural practices used in plantation ecosystems, and both are expected to influence soil respiration (RS). However, little is known about how the two practices, particularly their interaction, affect the heterotrophic (RH) and autotrophic (RA) components of RS. This knowledge gap further constrains our accurate evaluation on the carbon balance in plantations upon both thinning and understory removal, because the two practices are often conducted simultaneously in plantation management. Thus, we partitioned RS into RH and RA using trenched plots in a Chinese fir (Cunninghamia lanceolata) plantation subject to thinning and understory removal. The RS and its two components were measured in 2013 and 2014 at approximately monthly intervals. The potential control factors such as soil temperature, soil moisture and soil chemical properties were also determined. We found that thinning marginally significantly (P = 0.059) increased RS in 2013 by 17.32%, while it had no influence on RS in 2014 (P > 0.1), indicating that the influence of thinning on RS weakened with time. Similarly, a significant increase in RH toward thinning also occurred in 2013 (by 32.5%) but not in 2014. However, RA showed no response to thinning in either year. No interaction effect between thinning and understory removal was found on RS, RH, and RA. The increased soil temperature in the thinned stands in 2013 played a key role in raising the post-thinning RH and RS in this year. Generally, the temperature sensitivity (Q10) value of RS and its components increased in the order of RH < RS < RA regardless of treatment. The Q10 value of RS showed negligible variation among different treatments, and thus was likely not affected by thinning, understory removal, or their interactions. The results highlighted that understory removal in thinned stands would not exacerbate soil carbon emission in this plantation. •The effect of thinning on the soil respiration (RS) weakened over time.•The response of RS to thinning was mainly driven by the heterotrophic respiration.•Soil temperature played a key role in regulating the effect of thinning on the RS.•No interaction between understory removal and thinning was found on the RS.